Numbering Israel: A Rhetorico-Structural Analysis of Numbers 1-4 - Lunn, Nicholas P. (2010)
This article presents a section by section rhetorico-structural analysis of the opening chapters of Numbers, which deal with the counting and grouping of the people of Israel. The analysis reveals the employment throughout of literary patterns of both linear and inverted forms. The findings of such an analysis point to a purposively and intricately designed textual organization in which the patterning serves definable literary and rhetorical purposes, notably the marking of closure, the underlining of salient information, and the preparation for subsequent information. These findings are consistent with other similar structural studies of Old Testament texts.
Keywords: Levites; Parallelism; Chiasmus; literary structure; tribes of Israel; Census; Numbers